Preliminary exploratory research on the application value of oral and intestinal meta-genomics in predicting subjects' occupations–A case study of the distinction between students and migrant workers - Dou, Shujie; Ma, Guanju; Liang, Yu; Fu, Guangping; Shen, Jie; Fu, Lihong; Wang, Qian; Li, Tao; Cong, Bin; Li, Shujin (Frontiers in Microbiology, 2024)
Background: In the field of forensic science, accurately determining an individual's occupation can greatly assist in resolving cases such as criminal investigations or disaster victim identifications. However, estimating occupation can be challenging due to the intricate relationship between occupation and various factors, including gender, age, living environment, health status, medication use, and lifestyle habits such as alcohol consumption and smoking. All of these factors can impact the composition of an individual's oral or gut microbial community. Methods and results: In this study, we collected saliva and feces samples from individuals representing different occupational sectors, specifically students and manual laborers. We then performed metagenomic sequencing on the DNA extracted from these samples to obtain data that could be analyzed for taxonomic and functional annotations in five different databases. The correlation between occupation with microbial information was assisted from the perspective of α and β diversity, showing that individuals belonging to the two occupations hold significantly different oral and gut microbial communities, and that this correlation is basically not affected by gender, drinking and smoking, in our datasets. Finally, random forest (RF) models were built with recursive feature elimination (RFE) processes. Models with 100% accuracy in both training and testing sets were constructed based on 4 species in saliva samples or on a single pathway annotated by KEGG database in fecal samples, namely "ko04145" or Phagosome. Conclusions: Although this study may have limited representativeness due to its small sample size, it provides preliminary evidence of the potential of using microbiome information for occupational inference.